Cryotherapy Intervention to Reduce Cannulation Pain in Hemodialysis Patients - Giri Susanto; Wati Jumaiyah; Siti Latipah; Fitrian Rayasari (GLOBAL HEALTH SCIENCE GROUP, 2025)
End-stage chronic kidney disease requires hemodialysis with vascular access via an arteriovenous fistula (AVF). AVF cannulation is often painful. Cryotherapy, a cold therapy that can reduce pain through gate control theory, is used. Objective to assess the effectiveness of cryotherapy in reducing pain during arteriovenous fistula (AVF) puncture in hemodialysis patients. This study applied an Evidence-Based Nursing Practice approach, including a literature search through PubMed and ProQuest databases. The primary reference used was a systematic review and meta-analysis entitled